Pengaruh Pemahaman Kode Etik, Komitmen Organisasi, Prinsip Moral terhadap Kepuasan Kerja dengan Perilaku Etis - Yani Riyani; Khamim Khamim; Oscar Rynandi (Eksos, 2017)
This study aims to determine the effect of understanding the code of ethics, organizational commitment, moral principles to job satisfaction with ethical behavior as intervening variables. This research is a descriptive research in the form of correlation using data collection instrument in the form of questionnaire. 60 distributed questionnaires distributed proportionally to Lecturers in eight departments in the Polytechnic of Pontianak. The analytical tool used is the regression analysis, because it uses the questionnaire then tested the validity and reliability, then tested the classical assumptions before Hypothesis Testing done. This research resulted that both partially and simultaneously that the understanding of code of ethics, organizational commitment and moral principle influence ethical behavior while the understanding of ethical code, organizational commitment and moral principle in parsil have no effect on job satisfaction, while ethical behavior partially influence to job satisfaction but simultaneously understanding the code of ethics, organizational commitment, moral principles and ethical behavior affect the job satisfaction.